Intensitas Serangan Penyakit dan Pertumbuhan Tanaman Kacang Hijau (Vigna radiata L.) dengan Aplikasi Trichokompos yang Dikombinasi POC-Plus - Abdul Rahman; Jumar Jumar; Riza Adrianoor Saputra (Universitas Lambung Mangkurat, 2020)
The study aims to find out the effect of interaction between Trichokompos applications with POC-plus on the intensity of disease attack and green bean plant growth and to find out the Trichokompos dose and the best POC-plus application interval in suppressing disease attacks and increasing green bean plant growth and to find out the best dose of Trichokompos in suppressing disease attacks and increasing green bean plant growth and to find out the best POC-plus application interval in suppressing disease attacks and increasing green bean. This design of research uses a two-factor randomized design of groups (RAK). First factor is Trichokompos (T) with 3 which Taraf is 0 tons/ha Trichokompos, 5 tons/ha Trichokompos and 10 tons/ha Trichokompos and second factor is POC-plus application (P) with 4 which Taraf is 0 times POC-plus application, 2 times POC-plus, 3 times POC-plus application, 4 times POC-plus application which is repeated3 times. Research result shows that the effect of Trichokompos interaction and POC-plus application exerts an influence on the growth of the number of 15 hst age leaves whereas the influence of single factor Trichokompos is present in the high variable of 45 hst age plant, the number of leaves ages 15 hst and 30 hst, age leaf width 30 hst and 45 hst. But on the Trichokompos of POC-plus applications exert no influence on plant high growth, leaf count and leaf width as well as disease attack.